Relationship between Decrease in Urine Output following Treatment with Prostaglandin Inhibitors and PDA Closure - Goel, Malika; Dutta, Sourabh; Saini, Shiv Sajan; Sundaram, Venkataseshan (American Journal of Perinatology, 2022)
Objective Prostaglandin inhibitors are used for the treatment of patent ductus arteriosus (PDA) and they often transiently decrease the urine output (UO) due to prostaglandin inhibition in the renal vasculature. We hypothesized that preterm infants whose renal vasculature shows greater sensitivity to prostaglandin inhibitors are likely to have ductal tissue with greater sensitivity to the same. Our objective was to determine whether the decrease in UO following treatment of PDA with a prostaglandin inhibitor is associated with a higher probability of PDA closure.Study Design In a prospective, proof-of-concept, cohort study, we enrolled 40 preterm neonates with hemodynamically significant PDA (hsPDA), being treated with a prostaglandin inhibitor. The key predictor, UO, was measured at baseline and daily until 72 hours. We repeated echocardiography daily until PDA closure or the end of treatment. The key outcome was PDA closure. We compared “PDA-closed” (n = 28) and “PDA-open” (n = 12) groups for change in UO from baseline.Results The median (Q1, Q3) percent decrease in UO (figures rounded off to integers) was greater in the “PDA-closed” versus “PDA-open” group: from baseline to 0 to 24 hours [−45% (−55%, +0.04%) vs. −15% (−28%, +49%)]; baseline to 24 to 48 hours [−41% (−53%, +14%) vs. −3% (−25%, +62%), p = 0.03] and baseline to 48 to 72 hours [−33% (−49%, +32%) vs. +21% (−7%, +98%), p = 0.02]. Decrease in UO preceded PDA closure. The “PDA-closed” group had significantly greater weight loss, despite a greater decrease in UO. A decrease in UO of 27 and 17% by 24 to 48 hours and 48 to 72 hours, respectively, best predicted PDA closure.Conclusion A decrease in UO after treating hsPDA with a prostaglandin inhibitor is associated with successful closure of PDA.Key Points
Keywords: patent ductus arteriosus; preterm; prostaglandin inhibitor; oliguria